TIPOLOGI PROTOKOL PEMILIHAN KARYA SASTERA DALAM PEMBELAJARAN BIDANG ESTETIKA BAHASA KADAZANDUSUN - Henry Bating; Rosy Talin; Abdullah, Mohd Khairuddin @ Jerry; Mosin, Musirin (SARJANA, 2024)
ABSTRAK Kepelbagaian indikator pemilihan karya sastera dalam pembelajaran bahasa menimbulkan kekeliruan dalam menentukan bahan yang sesuai untuk pembelajaran Bidang Estetika (BE) bahasa Kadazandusun di sekolah peringkat menengah atas. Demi mengatasi kekeliruan itu, rangkuman indikator dan sub-indikator dari pelbagai sumber kepustakaan dan temu bual dijalankan. Tinjauan kepustakaan umum dan kepustakaan khusus Kadazandusun dijalankan untuk memperoleh data-data naratif indikator dan sub-indikator. Manakala temu bual diadakan dengan guru-guru bahasa Kadazandusun untuk mendapatkan maklum balas berbentuk data naratif tentang kaedah yang mereka gunakan untuk memilih karya sastera. Berdasarkan data-data naratif indikator dan sub-indikator yang diperoleh, rangkuman dijalankan dengan menggunakan kaedah Conventional Content Analysis (CCA). Analisis dijalankan untuk mengkategori tema-tema indikator dan sub-indikator. Rangkuman yang dihasilkan dari analisis CCA dibangun menjadi Tipologi Protokol Pemilihan Karya (TPPK) sastera Kadazandusun. Hasil rangkuman menunjukkan terdapat enam (6) indikator dan 133 sub-indikator dalam TPPK. Enam indikator itu terdiri daripada bahasa, sastera, guru, pelajar kurikulum dan budaya masyarakat. Sementara 133 sub-indikator terangkum dalam indikator bahasa (16), sastera (36), guru (35), pelajar (24), kurikulum (9) dan budaya masyarakat (13). Berdasarkan pengkategorian tema dari sumber kepustakaan khusus dan temu bual guru, maka indikator dan sub-indikator TPPK memiliki kontekstualiti sebagai kriteria pemilihan karya sastera untuk pembelajaran BE bahasa Kadazandusun. Seterusnya TPPK digunakan untuk menganalisis kandungan karya sastera Kadazandusun genre puisi dan prosa untuk memilih karya yang sesuai sebagai bahan pembelajaran BE bahasa Kadazandusun di sekolah peringkat menengah atas. ABSTRACT The diversity of indicators for selecting literary works in language learning creates confusion in determining suitable materials for teaching the Aesthetic Field (BE) of the Kadazandusun language at the upper secondary level. To address this confusion, a synthesis of indicators and sub-indicators from various sources of literature review and interviews was conducted. A general literature review and specific Kadazandusun literature were carried out to gather narrative data on the indicators and sub-indicators. Interviews were conducted with Kadazandusun language teachers to obtain narrative feedback regarding the methods they use to select literary works. Based on the narrative data obtained from the indicators and sub-indicators, a synthesis was conducted using the Conventional Content Analysis (CCA) method. The analysis was performed to categorize the themes of the indicators and sub-indicators. The synthesis resulting from the CCA analysis was developed into the Kadazandusun Literary Work Selection Protocol Typology (TPPK). The synthesis revealed that there are six (6) indicators and 133 sub-indicators in the TPPK. These six indicators consist of language, literature, teachers, students, curriculum, and community culture. Meanwhile, the 133 sub-indicators are categorized under the language (16), literature (36), teacher (35), student (24), curriculum (9), and community culture (13) indicators. Based on the categorization of themes from the specific literature sources and teacher interviews, the indicators and sub-indicators of the TPPK possess contextuality as criteria for selecting literary works for teaching the BE of the Kadazandusun language. The TPPK is then used to analyse the content of Kadazandusun literary works in the genres of poetry and prose to select suitable works as teaching materials for the BE of the Kadazandusun language at the upper secondary level.